Structural-semantic features of commercial terminolexic (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article examines the structural-semantic features and etymological features of the terminology "Financial and commercial activity" in the Uzbek language. The excessive number of differences between Uzbek terminology and other languages is explained by the existence of temporary ethno-cultural spaces in it, one of their main features is the possibility of elimination in certain extralinguistic conditions.